Nutrikinetic modeling reveals order of genistein phase II metabolites appearance in human plasma. Issue 11 (22nd August 2014) - Smit, Suzanne; Szymańska, Ewa; Kunz, Iris; Roldan, Victoria Gomez; van Tilborg, Marcel W. E. M.; Weber, Peter; Prudence, Kevin; van der Kloet, Frans M.; van Duynhoven, John P. M.; Smilde, Age K.; de Vos, Ric C. H.; Bendik, Igor
<x xml:space="preserve">Abstract</x> Scope Genistein from foods or supplements is metabolized by the gut microbiota and the human body, thereby releasing many different metabolites into systemic circulation. The order of their appearance in plasma and the possible influence of food format are still unknown. This study compared the nutrikinetic profiles of genistein metabolites. Methods and results In a randomized cross‐over trial, 12 healthy young volunteers were administered a single dose of 30 mg genistein provided as a genistein tablet, a genistein tablet in low fat milk, and soy milk containing genistein glycosides. A high mass resolution LC‐LTQ‐Orbitrap FTMS platform detected and quantified in human plasma: free genistein, seven of its phase‐II metabolites and 15 gut‐derived metabolites. Interestingly, a novel metabolite, genistein‐4′‐glucuronide‐7‐sulfate (G‐4′G‐7S) was identified. Nutrikinetic analysis using population‐based modeling revealed the order of appearance of five genistein phase II metabolites in plasma: (1) genistein‐4′, 7‐diglucuronide, (2) genistein‐7‐sulfate, (3) genistein‐4′‐sulfate‐7‐glucuronide, (4) genistein‐4′‐glucuronide, and (5) genistein‐7‐glucuronide, independent of the food matrix. Conclusion The conjugated genistein metabolites appear in a distinct order in human plasma. The specific early appearance of G‐4′, 7‐diG suggests a multistep formation process for the mono and hetero genistein conjugates, involving one or two deglucuronidation steps.